Prophylactic Use of Troxerutin Can Delay the Development of Diabetic Cognitive Dysfunction and Improve the Expression of Nrf2 in the Hippocampus on STZ Diabetic Rats - Songyun Zhang; Lingling Yuan; Lihui Zhang; Caige Li; Jie Li (Behavioural Neurology)
Background. With the change in lifestyle and the aging population, the incidence of cognitive dysfunction in diabetes mellitus is rising sharply. Oxidative stress is an important mechanism in the development of diabetic cognitive dysfunction. Nuclear factor E2-related factor 2 (Nrf2) is the core transcription factor of antioxidative stress. Early prevention and treatment of diabetic cognitive dysfunction can reduce the incidence of dementia and improve the quality of life of diabetic patients. Aim. This study was aimed at determining effect of troxerutin on the development of cognitive dysfunction and the expression level of Nrf2 in the hippocampus of streptozotocin (STZ) diabetic rats, when used in the early preventive stage. Methods. An STZ-induced diabetic rat model was established (n=30), and the animals were randomly divided into 2 groups: diabetic control group (DC, n=15) and diabetic troxerutin intervention group (DT, n=15). Another 10 normoglycemic rats were put into a normal control group (NC, n=10). While the DT group was injected with troxerutin (60 mg/kg), the DC group and the NC group were injected with physiological saline for 12 weeks daily. Learning and memory behaviors were tested using the Morris water maze test. The superoxide dismutase (SOD) activity, malondialdehyde (MDA) content, mRNA level, and protein level of Nrf2 were measured. Data were collected and analyzed by the statistical software package SPSS 19.0, which included one-way analysis of variance with completely randomized design. Results. Learning and memory levels were significantly improved in the DT group compared with the DC group. Moreover, in the DT group, the expression level of Nrf2 in the hippocampus was increased, activity of SOD was elevated, and MDA content was decreased. Conclusion. Prophylactic use of troxerutin delays the development of diabetic cognitive dysfunction and increases the expression level of Nrf2 in the hippocampus of STZ diabetic rats.